Cicero, Classicism, And Popular Culture - Gottesman, Melinda (Teaching History: A Journal of Methods, 2007)
Part memoir, part scholarly treatise, part travelogue, the late Marshall Fishwick’s last work is above all a deeply personal labor of love. Fishwick, a professor emeritus at Virginia Tech, is credited with being a pioneer in the field of Popular Culture Studies. He was the co-founder of the Popular Culture Association and founder of International Popular Culture, a key journal in the field.